2012
DOI: 10.5539/jas.v4n9p31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen and Sulphur Levels on Yield, Economics and Quality of QPM Hybrids under Dryland Condition of Eastern Uttar Pradesh, India

Abstract: The effect of four nitrogen levels {0 kg N ha -1 (N 0 ), 50 kg N ha -1 (N 1 ), 100 kg N ha -1 (N 2 ) and 150 kg N ha -1 (N 3 )} two QPM hybrids {Shaktiman-2 (G 1 ) and Shaktiman-4 (G 2 )} and three levels of sulphur { 15 kg S ha -1 (S 1 ), 30 kg S ha -1 (S 2 ) and 45 kg S ha -1 (S 3 )} in quality protein maize (QPM) production for two years on an experimental field (Sandy clay loam) located at Agricultural Dryland Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, India. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 7 publications
5
36
0
Order By: Relevance
“…However, length of cobs with and without husk recorded maximum values in treatment T 11 may be due to optimum availability of nitrogen and sulphur and better translocation of these nutrients to the reproductive parts. These findings are in accordance to those of Rasheed et al, (2004), Jeet et al, (2012), Qahar and Ahmad (2015) and Alam et al, (2003).…”
Section: Methodssupporting
confidence: 83%
“…However, length of cobs with and without husk recorded maximum values in treatment T 11 may be due to optimum availability of nitrogen and sulphur and better translocation of these nutrients to the reproductive parts. These findings are in accordance to those of Rasheed et al, (2004), Jeet et al, (2012), Qahar and Ahmad (2015) and Alam et al, (2003).…”
Section: Methodssupporting
confidence: 83%
“…Application of phosphorus with 100 kg P 2 O 5 ha -1 produced significantly the taller plants (185.95 cm), maximum LAI (3.17), dry matter production (10572 kg ha -1 ) while these growth parameters was minimum in unfertilized plots and significantly higher than other "p" levels (60, 80 kg P 2 O 5 ha -1 ). The nitrogen has beneficial effect on plant metabolism which affect physiological process of the crop and thereby increases the growth parameters [Jeet et al, 2012]. Likewise effect of high phosphorus levels on growth parameters were probably due to better development of root system and nutrient absorption [Masood et al, 2011].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of sulphur fertilization appears to vigorous plant as it presence in plant suggest greater availability of metabolites and nutrients ( ). Table 1 Kumar and Bohra 2014and Jeet et al, 2014Kumar et al, 2016Shivran et al 2013 Fig . 1-4 Jeet et al, Shivran et al 2013 Kumar and Bohra 2014 and Rs.80,310 ha ), was found to be higher with application of 150 kg N/ha( ).…”
Section: Nutrient Uptakementioning
confidence: 99%
“…The experiment results at various places indicated that highest grain yield was obtained with applied of 120 kg N/ha ( ). In recent past high yielding single cross hybrid of quality protein maize were Zea mays L. Kumar et al, 2015Jeet et al, 2014Baral et al, 2016Kumar et al, 2015and Kumar et al, 2016Jeet et al,2014Kumar et al, 2016Meena et al, 2011 bread by additional of opaque-2 mutant gene, which improved the lysine and tryptophan and reduced lucine and isoleucine content and produced quality protein with balanced composition of amino acids The quality protein maize has widely adopted for cultivation in developing world to fight malnutrition. The hypothesis of undertaken experiment assumed that nitrogen and sulphur, whose deficits are found in majority of loamy sand soil, can exert an effect on yield ( ).…”
Section: Maize (mentioning
confidence: 99%